The Evaluation of the Cylindrical Accuracy in Bore Honing of EN-GJL-250 Lamellar Cast Iron - István Sztankovics, (International Journal of Integrated Engineering, 2025)
The study of the different parameters, which describe the shape accuracy of the machined parts is important on functionally significant surfaces. The cylindrical accuracy is an essential characteristic of the machined bores of internal combustion engine blocks. The aim of the ongoing study is to explore the relationship between the shape error of the produced inner cylindrical surfaces and the setting parameters in honing. The results contribute to a wider understanding of the achievable precision of the examined finishing process by examining the relationships that have not been determined so far. In this paper, four parameters describing the cylindrical error after the honing procedure are analysed on EN-GJL-250 lamellar cast iron workpieces. The 23 factorial design is applied in the planning of experiments. Two levels of grain size, feed rate and pressure between the workpiece and the honing tool were chosen for the comprehensive analysis of the internal cylindrical honing process. The values of cylindricity, the valley maximum departure, the peak maximum departure and the cylinder taper are measured by the application of a Talyrond 365 accuracy measuring equipment. Equations were determined for the calculation of the studied parameters according to the full factorial design method. The results were evaluated in three steps: first the main effect of the process parameters are determined, then the presented equations are validated through control experiments. Finally, the detailed analysis of the results showed the alteration of the cylindrical correctness in function of the different parameters.